Early career achievement award: Supplementing omega-6 fatty acids to enhance early embryonic development and pregnancy establishment in Bos indicus and B. taurus beef cows - Cooke, Reinaldo F. [UNESP] (Oxford University Press (OUP), 2019)
Our research group investigated the impacts of supplementing Ca salts of soybean oil (CSSO), a source of omega-6 fatty acids (FAs), on reproductive performance of beef cows. Initial studies were conducted with Nelore (Bos indicus) cows grazing tropical pastures. Cows were assigned to fixed-time artificial insemination (AI) and supplemented or not with 100 g/d (as-fed basis) of CSSO, and supplementation regimens ranged from days-11 to 28 relative to AI. Overall, CSSO supplementation during the 21 d after AI increased (P < 0.01) pregnancy rates from 38.1% (623/1,635 as pregnant/total nonsupplemented cows) to 49.0% (843/1,720 as pregnant/total CSSO-supplemented cows), and these outcomes were associated with enhanced early embryonic development and pregnancy establishment when omega-6 FA were supplemented. To verify this rationale, our group compared FA incorporation in grazing Nelore cows (n = 90) supplemented or not with CSSO (100 g/d; as-fed basis) beginning at fixed-time AI until slaughter at day 19 of gestation. Supplementing CSSO increased (P ≤ 0.05) incorporation of linoleic acid and its omega-6 derivatives in plasma, endometrium, corpus luteum, and conceptus, whereas the same responses were not observed (P ≥ 0.25) for omega-3 FA. Complementing these findings, grazing Nelore cows (n = 100) were supplemented or not with CSSO (100 g/d; as-fed basis) beginning at fixed-time AI, and assigned to transcervical uterine flush on day 15 of gestation. Supplementing CSSO increased (P ≤ 0.04) conceptus length (2.58 vs. 1.15 cm) and mRNA expression of interferon-tau (4.1-fold increase) and prostaglandin E synthase 2 (2.6-fold increase), which are critical regulators of pregnancy establishment. These outcomes were recently replicated in B. taurus beef cows consuming temperate forages. Pregnancy rates were greater (P = 0.01) in Angus cows receiving CSSO (100 g/d; as-fed basis) for 21 d after fixed-time AI (60.2%; 226/383 as pregnant/total cows) compared with nonsupplemented cows (51.7%; 193/388 as pregnant/total cows). Supplementing CSSO to Angus × Hereford cows (n = 96) beginning after AI also increased (P = 0.05) mRNA expression of interferon-tau in day 15 conceptuses (1.8-fold increase). Collectively, our research demonstrated that post-AI CSSO supplementation favors incorporation of omega-6 FA into maternal and embryonic tissues, which enhances interferon-tau synthesis by the conceptus and increases pregnancy rates to fixed-time AI in B. indicus and B. taurus beef cows.
Keywords: beef cows; Ca salts of soybean oil; omega-6 fatty acids; pregnancy